RESCHEDULING USING THE PDM METHOD WITH MICROSOFT PROJECT 2021 IN THE URBAN SLUM QUALITY IMPROVEMENT PROJECT FOR AIR SANTRI, BANJAR REGENCY - Naura Rasyida Nurcahya; Candra Yuliana; Endah Widiastuti (Universitas Lambung Mangkurat, 2023)
In project development planning is a measure of the success of a project, which can determine the allocation of funds, time and quality to be obtained. This planning is combined with the use of special planning software, namely Microsoft Project 2021, which with this software can help make rescheduling easy and can track developments in the field. The data was analyzed using the Precedent Diagram Method (PDM) using the Microsoft Project 2021 application and the resulting plan is a network of all project work scopes. The results of the scheduling analysis of the Air Santri Urban Slum Quality Improvement Project, Banjar Regency, using the Microsoft Project 2021 application is that the project was carried out for 335 days obtained based on the scope of work with the largest duration of this project, namely 12 months 25 days starting on May 21 2021 ending on June 15, 2022. The total duration for each scope of work is Public Open Space (RTP) for 331 days, Retaining Walls (DPT) for 335 days, Roads for 139 days, Pier for 96 days, Waste Management Area (TPS) 170 days duration, SPAL DT 57 days duration and Clean water installation 201 days duration. Keywords: Microsoft Project 2021, Precedence Diagram Method (PDM), scheduling.